Interrogating infanticide/ Child euthanasia in the Roman christian era, vis-a-vis the Abuja practice (2013)
The purpose of this paper is an attempt to examine infanticide practices in the roman christian era and intetrrogate infanticide and child euthanasia in the same era. It alsoattempts to point out infanticide practies in abuja and makes a distinction between infanticide and child euthanasia in abuja. the study employed historical and comparative methodologies to highlight the issuees surrounding infanticde/chid euthanasia in the roman christian era and infanticide in abuja. A deliberate attempt at population reduction and man This paper , interrogated the role and pressures of culture over marital love and fidelity and vice-versa in both societies. The study employed historical and comparative methodologies to highlight the influence of culture over on ancient rome were classical and modern authors. Inscriptions from the corpus inscriptionumm latinarum (CIL) were also utilized. For Ugboha. Information was gathered from literary works, and oral interviews. The data were subjected to contect analysis.This paper argued that culture which has the capacity to influence peoples action with regard to marriage , intended to become partial and in times of change , becomes dynamic in order to suit the needs of contemporary times. This paper concludes by saying that in spite of the Hamitic hypothesis, culture and people of a society can grow and develop independence of each other. This paper , interrogated the role and pressures of culture over marital love and fidelity and vice-versa in both societies. The study employed historical and comparative methodologies to highlight the influence of culture over on ancient rome were classical and modern authors. Inscriptions from the corpus inscriptionumm latinarum (CIL) were also utilized. For Ugboha. Information was gathered from literary works, and oral interviews. The data were subjected to contect analysis.This paper argued that culture which has the capacity to influence peoples action with regard to marriage , intended to become partial and in times of change , becomes dynamic in order to suit the needs of contemporary times. This paper concludes by saying that in spite of the Hamitic hypothesis, culture and people of a society can grow and develop independence of each other. This paper , interrogated the role and pressures of culture over marital love and fidelity and vice-versa in both societies. The study employed historical and comparative methodologies to highlight the influence of culture over on ancient rome were classical and modern authors. Inscriptions from the corpus inscriptionumm latinarum (CIL) were also utilized. For Ugboha. Information was gathered from literary works, and oral interviews. The data were subjected to contect analysis.This paper argued that culture which has the capacity to influence peoples action with regard to marriage , intended to become partial and in times of change , becomes dynamic in order to suit the needs of contemporary times. This paper concludes by saying that in spite of the Hamitic hypothesis, culture and people of a society can grow and develop independence of each other. This paper , interrogated the role and pressures of culture over marital love and fidelity and vice-versa in both societies. The study employed historical and comparative methodologies to highlight the influence of culture over on ancient rome were classical and modern authors. Inscriptions from the corpus inscriptionumm latinarum (CIL) were also utilized. For Ugboha. Information was gathered from literary works, and oral interviews. The data were subjected to contect analysis.This paper argued that culture which has the capacity to influence peoples action with regard to marriage , intended to become partial and in times of change , becomes dynamic in order to suit the needs of contemporary times. This paper concludes by saying that in spite of the Hamitic hypothesis, culture and people of a society can grow and develop independence of each other. This paper , interrogated the role and pressures of culture over marital love and fidelity and vice-versa in both societies. The study employed historical and comparative methodologies to highlight the influence of culture over on ancient rome were classical and modern authors. Inscriptions from the corpus inscriptionumm latinarum (CIL) were also utilized. For Ugboha. Information was gathered from literary works, and oral interviews. The data were subjected to contect analysis.This paper argued that culture which has the capacity to influence peoples action with regard to marriage , intended to become partial and in times of change , becomes dynamic in order to suit the needs of contemporary times. This paper concludes by saying that in spite of the Hamitic hypothesis, culture and people of a society can grow and develop independence of each other